THE PREVENTION OF DIARRHEA IN TODDLER IN THE APOTEK WINNI FARMA AREA - Fauziah, Dewi Winni; Hesta, Hesta; Lestari, Muji Yati; Aprilianti, Rizka; Efriadin, Enjelsi; Anggela, Safitri Yega (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2023)
Diarrheal disease is a disease caused by the environment that can affect the health of mothers and toddlers. Based on health data for 2011, the incidence of diarrhea is still high with an IR of 303 per 1000 population. Riskesdas data for 2010, in a day around 460 (31.4%) died from diarrheal disease in toddlers. The prevalence of diarrhea is found more in rural areas than in urban areas. One of the factors causing the increased incidence of diarrhea is poor hygiene and environmental sanitation. The purpose of this activity is to provide knowledge to the public about the dangers and efforts to prevent diarrhea in toddlers